Cover Feature: N‐Aryl and N‐Alkyl Carbamates from 1 Atmosphere of CO2 (Chem. Eur. J. 72/2021). Issue 72 (13th December 2021) - Takeuchi, Katsuhiko; Chen, Ming‐Yu; Yuan, Hao‐Yu; Koizumi, Hiroki; Matsumoto, Kazuhiro; Fukaya, Norihisa; Choe, Yoong‐Kee; Shigeyasu, Shinji; Matsumoto, Seiji; Hamura, Satoshi; Choi, Jun‐Chul
Abstract : We have successfully isolated the zinc carbamate complex (phen)Zn(OAc)(OC(=O)NHPh) (1, phen=1, 10‐phenanthroline), which is an intermediate in the Zn(OAc)2 /phen‐catalyzed synthesis of organic carbamates from CO2, amines, and Si(OMe)4 . By analyzing the reaction mechanism based on the reactivity of 1 and DFT calculations, we improved the catalytic system and synthesized various organic carbamates—including polyurethane raw materials—by using CO2 at 1 atm. More information can be found in the Full Paper by J.‐C. Choi et al. (DOI: 10.1002/chem.202103587 ).